(untitled) (Acta Polytechnica CTU Proceedings, 2015)
In this work we present time-resolved photometry of several poorly-studied dwarf novae during recent superoutbursts. Observations were made with a CCD, mounted on 50- and 60-cm telescopes of the Sternberg Astronomical Institute in Crimea in April - May and October 2012 and June - July 2013. Superhumps were detected in light curves of all the dwarf novae. The amplitudes and periods of detected light variations were calculated. Superhumps evolution was also followed up for all systems and classification is improved.